Pengaruh Service Quality dan Relationship Marketing terhadap Customer Retention dengan Customer Satisfaction pada Cafe Yoikona Surabaya - Dwi Fitrianti; Siti Munajah; Achmad Yanu Alif Fianto (Transformasi Manageria: Journal of Islamic Education Management, 2024)
This study aims to determine the effect of Service Quality and Relationship Marketing on Customer Retention with Customer Satisfaction. The method used is quantitative. The number of samples in this study were 70 with respondents being consumers who had visited cafe yoikona Surabaya. Questionnaire distribution and data collection via google form. The data analysis technique in this study uses the SEM PLS approach. The test results found that service quality and relationship marketing have a significant positive effect on customer satisfaction at Cafe yoikona Surabaya, service quality has a significant positive effect on customer retention at Cafe yoikona Surabaya, relationship marketing has an insignificant positive effect on customer retention at cafe Yoikona Surabaya, customer satisfaction has a significant positive effect on customer retention at cafe yoikona Surabaya, service quality has a significant positive effect on customer retention through customer satisfaction at cafe Yoikona Surabaya, and relationship marketing has a significant positive effect on customer retention through customer satisfaction at cafe Yoikona Surabaya.